Worlding Tamil Cinema - Kunapulli, Amrutha (Taylor & Francis, 2025)
Worlding Tamil Cinema is a simultaneous intervention in the study of world cinema and the cinemas of India.With a focus on the globalising impulses of twenty-first-century Tamil cinema, the book explores the relationship between cinema, state, nationhood, and world cinema in the twenty-first century. On the one hand, the book argues for the limitations of studying Tamil cinema as "Indian" cinema by laying out the politics of nation, region, cinema, and statehood that have affected the cinemas of India, both in form and in content. In parallel, the book sets up a revised definition of world cinema as a category of cinema, revises the limits of world cinema as a field of film studies, and theorises the agentive process of “worlding." These interrelated discourses become the framework within which to study twenty-first-century Tamil cinema as world cinema. As such, the book provides a history of the Tamil film industry, as well as historical trajectories of the various narrative structures of Tamil cinema, which highlight the already global past of the industry, while using them as a foundation for the study of contemporary cinema and its global tendencies. The chapters study what have been considered unique features of Tamil cinema–the star system, the comedian and comedy track, and song sequence–and the way they have been changed to adapt to the globalist tendencies of non-native audiences and globalising sensibilities of native audiences, especially in the digital media era. This insightful volume will interest students and scholars of world cinema and cinemas of India, South Asian media and pop culture, and media scholars of the global south.